Biogeomorphic keystones and equivalents: Examples from a bedrock stream. Issue 8 (24th March 2020) - Jerin, Tasnuba; Phillips, Jonathan
Abstract: Biogeomorphic keystone species profoundly impact landscapes, such that their introduction or removal would cause fundamental changes in geomorphic systems. This paper explores the concept of biogeomorphic keystone species by examining the general vs. species‐specific biogeomorphic impacts (BGIs) of trees on a limestone bedrock‐controlled stream, Shawnee Run, in central Kentucky. Field investigation identified three strong BGIs: (i) biogeomorphic pool formation via bioweathering; (ii) root bank‐associated bioprotection; and (iii) avulsion‐originated island development linked to bioprotection. This research evaluates these impacts in the context of keystone or other biogeomorphic roles. A field survey was conducted on nine stream reaches, each consisting of 10–12 hydraulic units of riffle, pool, and run. Results suggest that American sycamore ( Platanus occidentalis ) plays a keystone role by promoting the development of ~42% of pools in the study area. While geomorphic pools are formed by fluvial process–form linkages, these biogeomorphic pools are developed by sycamore root‐induced channel bed bioweathering. Only American sycamore and chinquapin oak ( Quercus muehlenbergii ) exhibited root‐bank development amongst 15 different species identified – and thus play a vital role in bank bioprotection. Lastly, trees can promote avulsion‐originated island formation by creating erosion‐resistant bioprotective patches. Mature trees (in terms of size), particularly large American sycamore and chinquapin oak, dominate Shawnee Run islands with a mean diameter at breast height (DBH) > 40 cm. However, other trees can provide comparable bioprotection, particularly at mature stages. Because its absence would result in fundamentally different stream morphology, sycamore can be considered a biogeomorphic keystone species in Shawnee Run. © 2020 John Wiley & Sons, Ltd. Abstract : American sycamore ( Platanus occidentalis ) plays a biogeomorphic keystone role by root‐induced bedrock (BR) weathering, which promotes biogeomorphic pool development – a species‐specific biogeomorphic impact (BGI). Chinquapin oak ( Quercus muehlenbergii ) and American sycamore ( P. occidentalis ) exhibit root banks – when the root system creates the stream bank – and play role as autogenic bioconstructors . The bioprotective role of trees and subsequent bioconstruction promote development of avulsion‐originated islands – a role played by biogeomorphic equivalents linked to generalized biogeomorphic impacts.